2009
DOI: 10.1210/en.2008-1572
|View full text |Cite
|
Sign up to set email alerts
|

Life without Thyroxine to 3,5,3′-Triiodothyronine Conversion: Studies in Mice Devoid of the 5′-Deiodinases

Abstract: Considerable indirect evidence suggests that the type 2 deiodinase (D2) generates T(3) from T(4) for local use in specific tissues including pituitary, brown fat, and brain, whereas the type I deiodinase (D1) generates T(3) from T(4) in the thyroid and peripheral tissues primarily for export to plasma. From studies in deiodinase-deficient mice, the importance of the D2 for local T(3) generation has been confirmed. However, the phenotypes of these D1 knockout (KO) and D2KO mice are surprisingly mild and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(109 citation statements)
references
References 36 publications
5
99
1
4
Order By: Relevance
“…To further illustrate the potency of the homeostatic system preserving tissue T3 levels, mice lacking D1 or D2 (D1/D2 knock out mice) surprisingly, have normal circulating T3 levels due to TSH-induced T3 secretion from the thyroid, without a change in D3 mediated degradation, confirming the capacity of the hypothalamic-pituitary-thyroid axis to compensate for the lack of peripheral T4-to-T3 conversion (30).…”
Section: The Deiodinases In T3 Homeostasis Including Hypothyroidism mentioning
confidence: 97%
See 1 more Smart Citation
“…To further illustrate the potency of the homeostatic system preserving tissue T3 levels, mice lacking D1 or D2 (D1/D2 knock out mice) surprisingly, have normal circulating T3 levels due to TSH-induced T3 secretion from the thyroid, without a change in D3 mediated degradation, confirming the capacity of the hypothalamic-pituitary-thyroid axis to compensate for the lack of peripheral T4-to-T3 conversion (30).…”
Section: The Deiodinases In T3 Homeostasis Including Hypothyroidism mentioning
confidence: 97%
“…For example, in mice with D1 and D2 deficiency, the fact that serum T3 remains normal despite the absence of both the deiodinases, is related to the fact that the thyroid, rather than T4, is a much more important source of plasma T3 in rodents (30). Furthermore, hypothalamic-pituitary suppression occurs much sooner during illness or fasting in rodents than in humans, making extrapolation to the human situation even more difficult.…”
Section: Deiodinases and Non-thyroidal Illnessmentioning
confidence: 99%
“…7,8) It has been reported that the optimum dose of levothyroxine sodium for hypothyroid patients was related to body weight. 9) The homeostatic mechanisms for stabilizing thyroid hormone activity are complex and vary based on disease etiology, with many of the details unknown. Thus, therapeutic dosage should be optimized not only by body weight but also considering the variation of supply and turnover rates associated with the condition etiology.…”
mentioning
confidence: 99%
“…У мышей D1KO введение Т3 повышало его уровень в сыворотке и обусловливало более высокую сте-пень гипертиреоза, чем у мышей дикого типа. Сле-довательно, Д1 способна сглаживать последствия гипертиреоза и дефицита йода [16].…”
Section: биохимические и молекулярные свойства д1unclassified